Children's Ministry in October - Hamilton, Roddy (The expository times, 2008)
The article offers insights on telling the stories from Biblical passages that are ideal for the children's ministry and finding a way to respond to them. It suggests that the Ten Commandments could be read as part of an exercise imagining what the world could be like if only people worshipped God, loved parents and did not kill. In the passage Deuteronomy 34:4-12, which focuses on the death of prophet Moses, children are advised to be asked what does it feel like when they come over the hill or round the corner to see their home after a long journey.